Shape memory behavior of unidirectional pultruded laminate. (November 2021) - Korotkov, Roman; Vedernikov, Alexander; Gusev, Sergey; Alajarmeh, Omar; Akhatov, Iskander; Safonov, Alexander
Abstract: This study investigates the shape memory behavior of epoxy-based pultruded flat laminates reinforced with unidirectional glass fibers. To evaluate the shape memory performance of the composite material, a series of tests by bending flat specimens to the shape programming angle has been conducted. The shape fixity and shape recovery ratios for the pultruded composite specimens with 90° fiber orientation constituted 78.4% and 92.6%, respectively, and 13.3% and 91.9%, for specimens with 0° fiber orientation. The results obtained in this study show that the shape fixity and recovery ratios of the composite material are only slightly dependent on the shape programming angle and the number of shape memory cycles (up to 10 cycles). The study also determined the shape fixity and shape recovery ratios for cured resin specimens, which constituted 99.7% and 98.2%, respectively. To lay the foundation for further studies on the simulation and optimization of the pultrusion process, the resin cure kinetics, the thermomechanical and thermophysical properties of the cured resin, and the mechanical characteristics of the pultruded shape memory polymer composite were analyzed.